Analisis Korelasional Kecerdasan Emosional dan Spiritual dengan Kinerja Guru Madrasah Negeri di Bukittinggi - Lenny Novita; M. Arif; Hamdi Abdul Karim; Nunu Burhanuddin (Media Manajemen Pendidikan, 2026)
Teacher performance is an important factor in determining the quality of learning processes and outcomes in schools, which is not only influenced by pedagogic and professional competence, but also by internal factors such as emotional intelligence and spiritual intelligence. This study aims to analyze the relationship between emotional intelligence and spiritual intelligence with the performance of State Madrasah teachers in Bukittinggi City. This study uses a quantitative approach with a correlational method, with the population of all Madrasah teachers in Bukittinggi City and samples taken through stratified random sampling techniques. Data collection was carried out using questionnaires, while data analysis was carried out through various relevant statistical tests. The results showed that emotional intelligence and spiritual intelligence each had a positive and significant relationship with teacher performance, and together showed a strong relationship with teacher performance. These findings also indicate that spiritual intelligence has a more dominant role than emotional intelligence in improving teacher performance. Therefore, the development of emotional and spiritual intelligence needs to be a concern in an effort to improve the quality of teacher performance in the madrasah environment.